Importance of Mechanical Periodontal Therapy in Patients with Diabetes Type 2 and Periodontitis - Priscilla Naiff; Valéria Carneiro; Maria do Carmo Guimarães (International Journal of Dentistry)
Periodontitis is an infectious and inflammatory disease of high prevalence worldwide and constitutes a significant oral health problem. It can lead to tooth loss. In addition, the local inflammatory process can cause the release of inflammatory mediators in the bloodstream and, consequently, contribute to the emergence of systemic effects as cardiovascular and diabetic complications. The purpose of this mini review is to alert health professionals about the risk that periodontitis represents for the onset or exacerbation of complications in individuals with type 2 diabetes mellitus and to emphasize that the mechanical treatment of periodontal disease and reestablishment of oral health are essential for the metabolic control of these patients. The periodontal therapy may help to reduce the risk of systemic complications in diabetes patients. Proper dental management should be suggested by health professionals, mainly from physicians to their patients, in order to improve the health conditions in these individuals.